Gametogênese em peixes: aspectos relevantes para o manejo reprodutivo - Quagio-Grassiotto, Irani [UNESP]; Wildner, Daniel Dantas [UNESP]; Ishiba, Renata [UNESP] (My University, 2013)
In most of Teleostei fish gametogenesis is a cyclical and seasonal event. The renewal of the gametes, their development, differentiation, maturation and release provoke many alterations of gonadal features along the annual reproductive cycles. These alterations are used to recognize phases of the reproductive cycles. The recognition of these phases constitutes one of the parameters applied to the management of fisheries resources. Herein a recent proposal of the recognition of the reproductive phases in the Perciformes is exposed and its adaptation to the Neotropical Ostariophysi (Siluriformes and Characiformes) is provided. In addition, the gametogenesis in the Teleostei fish is briefly described.

Na maioria dos peixes Teleostei, a gametogênese é um evento cíclico e sazonal. A renovação dos gametas, seu desenvolvimento, diferenciação, maturação e liberação provocam várias alterações nas características das gônadas ao longo dos ciclos reprodutivos anuais. Essas alterações são utilizadas para reconhecer fases nos ciclos reprodutivos. O reconhecimento dessas fases constitui um dos parâmetros aplicados na gestão dos recursos pesqueiros. Este trabalho apresenta uma recente proposta de reconhecimento das fases reprodutivas desenvolvida para os Perciformes adaptada para os Ostariophysi neotropicais (Siluriformes e Characiformes). Soma-se a isso uma breve descrição da gametogênese nos peixes Teleostei.
Gametogenesis in fish: relevant aspects for the reproductive management
Keywords: Female; Fish; Gametogenesis; Male; Reproductive phases; Fases reprodutivas; Fêmeas; Gametogênese; Machos; Peixes